The impact of o, p`- DDT pesticide toxicity on the growth of Medaka fish embryo Oryzias latipes - Tong, Nguyen Xuan; Huong, Tran Thi Thu; Huong, Mai; Thuy, Duong Thi; Vy, Nguyen Hoang Thuy (Vietnam Journal of Marine Science and Technology, 2020)
The one-day-old O. latipes embryos is harvested and exposed to different concentrations of o, p`-DDT 0.04; 0.08; 0.12; 0.16; 0.2; 0.24; 0.28 and 0 µg/l (the control sample is not supplemented with o, p`-DDT) for 24, 48, 72 and 96 hours. After 24, 48, 72 and 96 hours, the results showed that LC50 value is gradually decreased, respectively 0.1013; 0.0772; 0.0486 and 0.0359 µg/l. The difference between LC50 values depends on the exposure concentration and exposure time. The results showed that the mortality rates of Medaka O. latipes increased with increasing pesticide concentrations as well as increasing exposure time. The experiment for observation of morphology and structure also found malformations in the spine and eyes of fish embryos. This chemical has strongly affected embryonic heart rate and embryonic morphology during growth and development.